2001
DOI: 10.1113/eph8601835
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Thyroxine (T4) and Triiodothyronine (T3) Transport in the Isolated Rat Heart

Abstract: Thyroid hormones are the iodized derivatives of the amino acid tyrosine and are synthesized by the thyroid gland. Thyroxine (T 4 ) and triiodothyronine (T 3 ) regulate the processes of general metabolism (oxidative phosphorylation), growth, development and specific gene expression (Oppenheimer & Schwartz, 1987;Samuels, 1988). About 90 % of the thyroid production is T 4 while 10 % is T 3 . It is thought that T 4 has little, if any, biological activity, and it is considered as a prohormone, which becomes activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This method allows the measurement of 3 H-histamineuptake (test molecule) in relation to 14 C-mannitol (as an extracellular reference molecule) during their passage through the coronary blood vessels [4649]. The lower values of 3 H-histamine recovery (i.e., histamine dilution profile curve) in relation to reference molecule reflect its uptake.…”
Section: Methodsmentioning
confidence: 99%
“…This method allows the measurement of 3 H-histamineuptake (test molecule) in relation to 14 C-mannitol (as an extracellular reference molecule) during their passage through the coronary blood vessels [4649]. The lower values of 3 H-histamine recovery (i.e., histamine dilution profile curve) in relation to reference molecule reflect its uptake.…”
Section: Methodsmentioning
confidence: 99%
“…This method measures the relative extraction (uptake) of the test molecule ( 125 I-LDL) in relation to an extracellular referent tracer ( 99m Tc-Nanocis, EBD) as it transits through the blood vessel (18,19). Transport parameters obtained from the rapid dual isotope dilution technique allow calculation of dynamics and understanding the mechanism of test molecule transport from intravascular space to the blood vessel wall.…”
Section: Rapid Dual -Isotope Dilution Methodsmentioning
confidence: 99%
“…27- 29 The results obtained using this method showed that the blood vessel wall uptake of 125 I-LDL had very low capacity and slow dynamics, hereof the protocol was changed and the continuous 10-min perfusion of the 125 I-LDL was applied (Steady state presents new experimental research using radiolabeled 125 I-LDL on an ex vivo isolated segment of carotid artery of cholesterolfed rabbits in order to research LDL uptake by the blood vessel at constant perfusion flow and pressure, and to estimate the influence of shear stress and atherogenic diet duration (prolonged hyperlipidemia) on the LDL uptake. Mathematical equations used in this work enabled us to precisely describe and predict some parameters in research.…”
Section: Steady State Methodsmentioning
confidence: 99%